Állami segítséggel történő startup finanszírozás nemzetközi tapasztalatai - Judit Karsai (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
– The government has an important role to play in financing each stage of development of startups. Most of the financing for startups is provided by non-reimbursable public grants and lending, the latter supported by government guarantees. The role of venture capital is much smaller. However, the government can also help with this, notably by co-invest with private investors and leverage the capital of private venture capital funds. An important tool to promote the recapitalization of venture capital funds is the government guarantee available to private investors in the funds. The most effective way for the government to finance startups is not by providing funds directly to companies, but by acting as a catalyst for funding by encouraging private players in the market. The analysis below shows which of the internationally developed solutions for government support have spread and with what success.
Keywords: L26; G23; G24; G38; H25; H81; M13; 330; Venture finance; Development finance; Entrepreneurship; Startup; Grant; Tax Credit; Loan; Loan Guarantee; Equity Finance; Mezzanine; Venture Capital; Business Angel